2000
DOI: 10.1021/ac000905v
|View full text |Cite
|
Sign up to set email alerts
|

A Battery-Powered Notebook Thermal Cycler for Rapid Multiplex Real-Time PCR Analysis

Abstract: A compact, real-time PCR instrument was developed for rapid, multiplex analysis of nucleic acids in an inexpensive, portable format. The instrument consists of a notebook computer, two reaction modules with integrated optics for four-color fluorescence detection, batteries, and a battery-charging system. The instrument weighs 3.3 kg, measures 26 x 22 x 7.5 cm, and can run continuously on the internal batteries for 4 h. Independent control of the modules allows differing temperature profiles and detection schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 21 publications
1
59
0
Order By: Relevance
“…Tests could be completed in as little as 16 min, with detection limits on the order of 10 2 -10 4 organisms/mL. A portable instrument incorporating a four-color fluorescence detection system was developed by the same group for rapid, multiplex real-time PCR [224]. Use of this instrument for rapid thermal cycling in a 25 mL volume allowed the characterization of a SNP in the hereditary hemochromatosis gene in about 20 min.…”
Section: Clinical Dna By Microchip Pcrmentioning
confidence: 99%
“…Tests could be completed in as little as 16 min, with detection limits on the order of 10 2 -10 4 organisms/mL. A portable instrument incorporating a four-color fluorescence detection system was developed by the same group for rapid, multiplex real-time PCR [224]. Use of this instrument for rapid thermal cycling in a 25 mL volume allowed the characterization of a SNP in the hereditary hemochromatosis gene in about 20 min.…”
Section: Clinical Dna By Microchip Pcrmentioning
confidence: 99%
“…[21] In 2001, a batterypowered notebook PCR instrument that performed rapid PCR analysis was developed. [22] Through independently controlled thermal cycler modules, rapid detection and identification of Bacillus subtilis and Bacillus thuringensis was observed. [22] The Handheld Advanced Nucleic Acid Analyzer (HANAA) is a battery-powered thermal cycler that utilizes silicon and platinum-based thermocycler units to perform four real time PCR reactions simultaneously.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…[22] Through independently controlled thermal cycler modules, rapid detection and identification of Bacillus subtilis and Bacillus thuringensis was observed. [22] The Handheld Advanced Nucleic Acid Analyzer (HANAA) is a battery-powered thermal cycler that utilizes silicon and platinum-based thermocycler units to perform four real time PCR reactions simultaneously. [19] HANAA can detect a variety of bacterial organisms via real time PCR.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…In this frame, since the first PCR was carried out on a chip (Kopp et al 1998), a large proliferation of biodevices with different geometries (single-or multiwell based) (Northrup et al 1998;Belgrader et al 2001;Neuzil et al 2006) and/or equipped with microfluidic systems (Shaikh et al 2005) have been reported. Several materials (e.g., silicon (Weiping et al 2005), quartz (Jacobson et al 1995), glass (Giordano et al 2001), ITO (Suna et al 2002), etc.)…”
Section: Introductionmentioning
confidence: 99%